Efectividad de la fertilización orgánica en el crecimiento y rendimiento del cultivo de arroz (Oryza Sativa l.) En la zona de San Roque-Charapotó - Pin García, Carlos Alejandro (2022)
The objective of the research was to evaluate the effectiveness of organic fertilization on the growth and yield of rice crops (Oryza sativa L.), in the San Roque-Charapotó area. The experiment was established with two fertilization treatments that were: Organic fertilization (T1) and conventional chemical (T2). In each experiment, 10 plots of 25 m2 were established. The main variables evaluated were aerial dry mass, root dry mass and paddy rice yield. Data were analyzed with Student's t-statistic for paired observations. The fertilization treatments significantly influenced (p<0.05) the aerial and root dry mass, where the conventional chemical fertilization reached the highest area dry mass, while the organic fertilization achieved the highest root dry mass. Paddy rice yield was not significantly (p<0.05) influenced by organic and conventional chemical fertilization treatments. Both treatments achieved paddy rice yield higher than 10 t ha-1. It is concluded that under the conditions where the experiment was developed, organic fertilization can be an effective ecological alternative to achieve yields similar to those achieved by conventional chemical fertilization